2017
DOI: 10.1002/14651858.cd008349.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality for stroke rehabilitation

Abstract: Background Virtual reality and interactive video gaming have emerged as recent treatment approaches in stroke rehabilitation with commercial gaming consoles in particular, being rapidly adopted in clinical settings. This is an update of a Cochrane Review published first in 2011 and then again in 2015. Objectives Primary objective: to determine the efficacy of virtual reality compared with an alternative intervention or no intervention on upper limb function and activity. Secondary objectives: to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

42
708
0
24

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 763 publications
(842 citation statements)
references
References 174 publications
42
708
0
24
Order By: Relevance
“…This space was set up in response to current evidence reporting the potential of VR for improving motor function and activity level in stroke and cerebral palsy [1,15]. Patients treated by our clinic include a variety of neurologic conditions, but primarily consists of cerebral palsy and traumatic brain injury.…”
Section: Kiosk Model For Pediatric Neurorehabilitation At Schön Clinimentioning
confidence: 99%
See 2 more Smart Citations
“…This space was set up in response to current evidence reporting the potential of VR for improving motor function and activity level in stroke and cerebral palsy [1,15]. Patients treated by our clinic include a variety of neurologic conditions, but primarily consists of cerebral palsy and traumatic brain injury.…”
Section: Kiosk Model For Pediatric Neurorehabilitation At Schön Clinimentioning
confidence: 99%
“…Over the last decade, interest in nonimmersive virtual reality (VR) for rehabilitation has led to the development of low‐cost systems capable of providing personalized task practice for the rehabilitation of motor impairment in clinical [1‐3] and home settings [4]. This field has grown partly due to technological advances in motion capture and cloud computing, making technologies more accessible for clinicians to test and developers in this field to produce content for.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After all, the goal is that patients’ speech improves, and if a patient's speech improves it might be better to make the thresholds for that patient somewhat more challenging; and vice versa if a patient's speech deteriorates. The literature on the personalisation of exergames also point in this direction (Goršič, Darzi, & Novak, ; Laver et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the greater effect of robotic or virtual reality rehabilitation rather than conventional rehabilitation is not sure. Cochrane systematic reviews on this topic concluded that “ virtual reality and physiotherapy may have similar effects on gait, balance, and quality of life ” for Parkinson disease [14] or that “ the use of virtual reality and interactive video gaming was not more beneficial than conventional therapy approaches in improving upper limb function ” after stroke [101]. When there is effect of robot-assisted training, the quality of evidence is very low or low for improving arm functions after stroke [102] or moderate for improving independent walking in people after stroke [103].…”
Section: Discussionmentioning
confidence: 99%